Determination of heat transfer parameters in absorbing thin films on substrate by the transient grating method - Ivakin, Evgeniy V.; Tolstik, Alexei L. (Journal of the Belarusian State University. Physics, 2023)
Advantages of the transient grating method for contactless study of thin-film materials have been demonstrated. Thin films of diamond-like carbon and thermoelectric lead telluride have been studied. Transient gratings are formed on a surface of film due to absorption of nanosecond pulsed laser radiation. The diffracted signal character enables the heat transfer parameters and thermal diffusivity determination. The transient grating period increase leads to transfer from thermal diffusivity of thin film measurements to its effective value determination, with a contribution made by the substrate. At large period of the grating one can realise measurements of thermal diffusivity of the substrate itself. Acoustic wave excitation in the near-surface thin layer of the air, which earlier has been considered as a factor distorting the diffracted signal dynamics is of special interest. In this case there is a possibility to temperature measurement of the film when it is heated by a laser pulse.
Keywords: holography; transient grating; heat transfer; thermal diffusivity; diamond-like carbon; lead telluride; thermoelectric; acoustic wave